Scarface and the untouchable : Al Capone, Eliot Ness, and the battle for Chicago - Collins, Max Allan; Schwartz, A. Brad (Austin Bradley) (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"A THRILLING MAGNUM OPUS ON AMERICA'S GREAT CRIME EPIC. A Mystery Writers of America "Grand Master"--author of the gangster classic Road to Perdition, long-time Dick Tracy writer, and multiple Shamus Award winner--teams with an acclaimed rising young historian, in this riveting, myth-shattering dual portrait of Al Capone, America's most notorious gangster, and Eliot Ness, the legendary Prohibition agent whose extraordinary investigative work crippled his organization. Written with novelistic pacing and underpinned by groundbreaking research, Max Allan Collins and A. Brad Schwartz's Scarface and the Untouchable delivers--at last--the definitive account of the "Battle for Chicago," the iconic struggle between the mythic yet real combatants who have captivated the world for 90 years"--